Association of the All-Patient Refined Diagnosis-Related Groups Severity of Illness and Risk of Mortality Classification with Outcomes. Issue 10 (October 2021) - Elgwairi, Emadeldeen; Yang, Shengping; Nugent, Kenneth
Abstract : The All-Patient Refined Diagnosis-Related Group risk of mortality (ROM) score and severity of illness (SOI) score provide a uniform classification of hospitalized patients available in many hospitals. This study included >18, 000 adult patients admitted to a tertiary care center during 1 calendar year. The associations of SOI and ROM levels with clinical information, including age, sex, admission shock index, admission glucose and lactate levels, length of stay, and mortality, were analyzed. Increases in SOI and ROM levels were associated with increased length of stay and increased mortality. The All-Patient Refined Diagnosis-Related Group classification system provides important information relevant to many aspects of clinical care and allows comparison within and between hospitals. Abstract : Objectives: Diagnosis-related groups (DRGs) is a patient classification system used to characterize the types of patients that the hospital manages and to compare the resources needed during hospitalization. The DRG classification is based on International Classification of Diseases diagnoses, procedures, demographics, discharge status, and complications or comorbidities and compares hospital resources and outcomes used to determine how much Medicare pays the hospital for each "product/medical condition." The All-Patient Refined DRG (APR-DRG) incorporated severity of illness (SOI) and risk of mortality (ROM) into the DRG system to adjust for patient complexity to compare resource utilization, complication rates, and lengths of stay. Methods: This study included 18, 478 adult patients admitted to a tertiary care center in Lubbock, Texas during a 1-year period. We recorded the APR-DRG SOI and ROM and some clinical information on these patients, including age, sex, admission shock index, admission glucose and lactate levels, diagnoses based on International Classification of Diseases, Tenth Revision discharge coding, length of stay, and mortality. We compared the levels of SOI and ROM across this clinical information. Results: As the levels of SOI and ROM increase (which indicates increased disease severity and risk of mortality), age, glucose levels, lactate levels, shock index, length of stay, and mortality increased significantly ( P < 0.001). Multiple logistic regression analysis demonstrated that each unit increase in ROM and SOI level was significantly associated with an 11.45 and a 10.37 times increase in the odds of in-hospital mortality, respectively. The C-statistics for the corresponding models are 0.947 and 0.929, respectively. When both ROM and SOI were included in the model, the magnitudes of increase in odds of in-hospital mortality were 5.61 and 1.17 times for ROM and SOI, respectively. The C-statistic is 0.949. Conclusions: This study indicates that the APR-DRG SOI and ROM scores provide a classification system that is associated with mortality and correlates with other clinical variables, such as the shock index and lactate levels, which are available on admission.